A numerical study on the influence of rebar cut-off on the shear performance of RC beam by using rigid-body-spring-method. (June 2022) - Fu, Li; Yin, Qiangsheng; Nakamura, Hikaru; Yamamoto, Yoshihito; Miura, Taito
Abstract: The purpose of this study was, on the one side, to evaluate the deterioration mechanism of the shear performance caused by rebar cut-off setting for RC beams, and on the other, to clarify the reinforcing mechanism of stirrups to shear against rebar cut-off setting. The shear performances of the beam specimens with and without cut-off point in longitudinal rebar were firstly evaluated by Three Dimensional Rigid-Body-Spring-Method (3D RBSM). Also, the reinforcing effect of stirrups on shear against rebar cut-off setting was simulated. Moreover, by utilizing the numerical stress results obtained from 3D RBSM, the developments of shear resistance components (i.e. beam and arch actions), together with the deflections, were quantitatively estimated at the critical stages. In the meantime, the change of the localized stresses in concrete and rebars, and crack patterns for each beam specimen was discussed in detail. As a result, the specimen with rebar cut-off represented a reduction of shear strength and ductile capability, compared with the uncut beam, but the application of stirrups to rebar cut-off zone could suppress the adverse effect from cut-off setting. Moreover, the deterioration mechanism of the shear performance caused by rebar cut-off and the reinforcing mechanism of stirrups were revealed, and the mechanical factors for the deterioration behaviors of the shear resistance components were explained. The above achievements could provide valuable reference to optimize the design of rebar cut-off for RC specimens.